Evaluation of Patients with Postoperative Pancreatic Fistula After Isolated Splenectomy: A Retrospective Study - Celik, Suleyman Utku; Demir, Mehmet Bahadir; Gulap, Yasin; Polat, Hilmi Erencan; Hidiroglu, Mehmet Mert; Ozkara, Murat; Kesikli, Sacit Altug (European Journal of Therapeutics, 2024)
Objective: Postoperative pancreatic fistula (POPF) is a potentially life-threatening complication. This complication occurs not only after pancreatic surgery but may also arise after other abdominal procedures. In this study, we aimed to determine the incidence and risk factors of POPF in patients undergoing isolated splenectomy. Methods: Patients who underwent isolated splenectomy were identified. POPF was defined according to the 2016 update of International Study Group of Pancreatic Fistula classification and graded as biochemical leak (BL), grade B fistula, and grade C fistula. Characteristics and perioperative variables were compared between patients who had pancreatic fistula and those who have not. Results: The study cohort consisted of 59 patients with median age 38.9 years, and 50.8% male. The indication was trauma in 18 (30.5%) patients. Twenty (33.9%) patients were operated upon emergently. Thirty-seven (62.7%) splenectomies were performed open. Out of all patients, 14 (23.7%) developed any sort of pancreatic fistula. BL occurred in 11 (18.6%) patients and 3 (5.1%) patients developed a grade B fistula. Comparison of patients with and without BL/POPF demonstrated no significant differences in demographics, surgical indication, operative method, surgical approach, or postoperative outcome. Conclusions: Despite higher incidence of pancreatic leak, the rate of clinically relevant fistula is relatively low. In this study, we did not identify any factors associated with BL/POPF. Thus, further studies are needed on pancreatic fistula after splenectomy.